The Impact of Advising on Degree Completion and Student Retention - Stevens, Jeff; Chen, Jiun-Shiu; Adrian, Mitch (IJRDO - Journal of Applied Management Science, 2018)
Graduation rates remain at low levels along with low retention rates and diminishing rates of students feeling connected to their school, which continue to be a major challenge for universities across the nation. This study will investigate the link to these factors and student sense of belonging as it relates to advisement at a university in southwest Louisiana with a student population of roughly 10,000 students. In many instances, advising has become-it-yourself” advising process that has plagued advising for some time for schools across the nation. When students are permitted to set up their own class schedule, several problems quickly emerge, which range from them selecting the wrong courses to selecting courses to fit time, not degree programs. The proliferation of online platforms creates a greater opportunity for students into a selfchecklist process, which increases problems related to self-advising, choppy advising and a greater potential for a disconnected student. The amount of time students spend with advisors are clear indicators of degree completion and the level of retention of students, which has long and short term benefits. Money is not the main reason students leave school as opposed to issues related to advisement and connection with the school, which are factors that can be addressed as will be illustrated in this paper. The main sections of this paper will be the foundational aspects of advising, the general advising atmosphere, student retention.